2022
DOI: 10.3389/fmicb.2022.1049525
|View full text |Cite
|
Sign up to set email alerts
|

Prevotella genus and its related NOD-like receptor signaling pathway in young males with stage III periodontitis

Abstract: BackgroundAs periodontitis progresses, the oral microbiota community changes dynamically. In this study, we evaluated the dominant bacteria and their roles in the potential pathway in young males with stage III periodontitis.Methods16S rRNA sequencing was performed to evaluate variations in the composition of oral bacteria between males with stage I and III periodontitis and identify the dominant bacteria of each group. Function prediction was obtained based on 16S rRNA sequencing data. The inhibitor of the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 52 publications
(72 reference statements)
2
3
0
Order By: Relevance
“…In our study, D. pneumosintes was detected more frequently in P subjects than in H subjects (p-value < 0.001). The results of our study are aligned with evidence from previous investigations of D. pneumosintes being associated with the oral microbiota of young adults and with advanced periodontal destruction [23][24][25]. A study by Ayala Herrera et al, in 2019, found that both F. alocis and D. pneumosintes were detected at higher frequencies (80% and 66.66%, respectively) in the Mexican population [47].…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…In our study, D. pneumosintes was detected more frequently in P subjects than in H subjects (p-value < 0.001). The results of our study are aligned with evidence from previous investigations of D. pneumosintes being associated with the oral microbiota of young adults and with advanced periodontal destruction [23][24][25]. A study by Ayala Herrera et al, in 2019, found that both F. alocis and D. pneumosintes were detected at higher frequencies (80% and 66.66%, respectively) in the Mexican population [47].…”
Section: Discussionsupporting
confidence: 92%
“…This study observed a significant association between clinical attachment loss and the presence of F. alocis and D. pneumosintes. The results of the study confirm the data from previous studies that have reported an increased prevalence of these bacteria with increased probing depths, higher clinical attachment loss, and increased disease severity [22,25,29,46,[55][56][57]. The F. alocis genotype, which has an enhanced virulence, is found to be significantly associated with increased probing depths and progressive attachment loss [56,58].…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Prevotella , a genus of Gram-negative bacteria, plays a significant role in the microbial ecosystem of the oral cavity ( 76 ). These non-motile, single-celled organisms flourish under anaerobic growth conditions ( 77 ).…”
Section: Oral Bacteria Associated With Osccmentioning
confidence: 99%